The Map of BMT in Brazil: A Public Access Panel to Hematopoietic Stem Cell Transplantation Data - Simione, Anderson João; Seber, Adriana; dos Santos, Rosana Machado; Talarico, Wiliam Odair; Malerba, Wagner; Compt, Livia Caroline Barbosa Mariano; Costa, Flavia Ferreira da; Loebel, Renata Rose; Dias, Carla Gonçalves; Villagra, Andressa; Duarte, Adriana Maria; Fernandes, Wagner; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
Brazil has a vast Hematopoietic Stem Cell Transplantation (HSCT) program with 126 teams and 86 Centers recognized by the Ministry of Health. Outcomes of these transplants are unknown. The objective of this work is to create a public database to help the public and health care professionals to find information on allogenic HSCT performed in Brazil. Methods: The team chose indicators, outcomes, and developed tools to accept secure data input using e-DBtC, Access, RedCap and excel spreadsheet. All data was inserted into the Virtual Analytics platform after careful validation and then presented as tables and graphics in separate portals for healthcare professionals and general public. Results: 29 HSCT centers participating in the project sent data on all consecutive allogeneic transplants performed between August 2019-2020. We gathered data from 943 transplants, with results arranged in graphs and tables, with the possibility of using various filters, so users can customize their search. In conclusion, more than 60% of all allogenic transplants performed in the country are now included in the Map of BMT, in an easy and accessible way to be searched. We hope to continue this initiative and extend it to other services, emphasizing great accomplishment of the Brazilian transplant community.